Pengukuran Kinerja Keuangan Pemerintah Kota Pontianak - Akhmad Yani; Zulkarnain Zulkarnain (UNHI Press, 2020)
Demands on performance and the implementation of the principle of performance accountability lead to the need to measure local government performance. Performance measurement is important to assess the accountability of officials or organizations in producing the best service to the public, as well as in realizing good governance in local governments. This study seeks to provide an overview of the financial performance of the Pontianak City Government by using performance measurement tools in the form of regional financial ratios. Quantitative approaches are used in data analysis. The narrative form is then descriptively applied to illustrate the findings from the results of the analysis of related data. From this research it was found that the Pontianak City Government is quite capable in financing the administration and development in the regions; PAD revenues increase from year to year; the contribution of local taxes is very large in the formation of overall PAD; dependence on transfers from the central and other regional governments, including the category of